Pengaruh Dukungan Keluarga terhadap Minat Baca Siswa Kelas IX MTs Nurul Islam Kota Kediri - Endang Fitraloka; Rini Risnawita Suminta; Dewi Hamidah (Happiness: Journal of Psychology and Islamic Science, 2022)
This study aims to determine the effect of family support on reading interest in class IX MTs Nurul Islam, Kediri. This study uses a quantitative approach. The sample in this study were 57 respondents. The sampling technique uses non-probability sampling in the form of purposive sampling. The research data analysis was carried out using linear regression analysis. Based on the results of research on family support for reading interest in class IX MTs Nurul Islam, Kediri, namely: the level of family support is in the moderate category and the level of students' reading interest is in the moderate category. Based on the results of the regression analysis, a sufficient/moderate (positive) relationship was obtained between family support and reading interest with a coefficient of determination of 20.9%. Thus it can be said that the influence of reading interest is influenced by family support by 20.9%, while the remaining 79.1% is influenced by other factors.